2019
DOI: 10.1002/jcp.28505
|View full text |Cite
|
Sign up to set email alerts
|

COPS5 negatively regulates goat endometrial function via the ERN1 and mTOR‐autophagy pathways during early pregnancy

Abstract: In ruminant, adequate endometrial function is a major factor affecting implantation and economic efficiency. However, the precise mechanisms regulating goat endometrial function during the peri‐implantation period of pregnancy are still unclear. Here, we investigated the functional role and signal transduction of the fifth component of the constitutive photomorphogenic‐9 signalosome (COPS5) in the regulation of endometrial function in endometrial epithelial cells (EECs). Our results showed that hormones decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…Thus, it is possible that Cops5 regulates the autophagy of Mtch2 by deubiquitinating Mtch2. In addition, it has been shown that Cops5 regulates autophagy via the ERN1 and mTOR pathways in goat endometrial epithelial cells (38). Given that Cops5 interacts with the mitochondrial protein Mtch2, the possibility is raised that Cops5 regulates mitophagy or, even more specifically, the autophagy of Mtch2.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that Cops5 regulates the autophagy of Mtch2 by deubiquitinating Mtch2. In addition, it has been shown that Cops5 regulates autophagy via the ERN1 and mTOR pathways in goat endometrial epithelial cells (38). Given that Cops5 interacts with the mitochondrial protein Mtch2, the possibility is raised that Cops5 regulates mitophagy or, even more specifically, the autophagy of Mtch2.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 E shows that the reduction in PGR and ESR1 was found compared with the shN group, but there were no significant differences in IFNAR1 and IFNAR2 between the shN and shBCL2L15 groups. We also found a knockdown of BCL2L15 reduced the expression of HOXA10 , HOXA11, and LIF , which served as the key markers for endometrial receptivity [ 19 , 23 ] ( Figure 2 F).…”
Section: Resultsmentioning
confidence: 85%
“…Endometrial receptivity is a prerequisite to render the uterus suitable for embryo adhesion and to establish pregnancy in ruminants [18,19]. Although the molecular mechanism of regulating endometrial receptivity remains unclear, it is well-documented that altered gene expression in EECs during early pregnancy guarantees the success of embryo implantation [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence indicates that autophagy shows a close relationship with the cell proliferation, angiogenesis, cell apoptosis, prostaglandin secretion and cell attachment of endometrial epithelial cells [ 27 , 28 , 29 ]. In particular, three recent studies have reported that autophagy appears to be the cruical pathway of endometrial regulation during early pregnancy in goat [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%